2013
DOI: 10.1128/aac.02109-12
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Nanoemulsion in Combination with Cetylpyridinium Chloride in Multidrug-Resistant Acinetobacter baumannii

Abstract: c Acinetobacter baumannii has emerged as a serious problematic pathogen due to the ever-increasing presence of antibiotic resistance, demonstrating a need for novel, broad-spectrum antimicrobial therapeutic options. Antimicrobial nanoemulsions are emulsified mixtures of detergent, oil, and water (droplet size, 100 to 800 nm) which have broad antimicrobial activity against bacteria, enveloped viruses, and fungi. Here, we screened the antimicrobial activities of five nanoemulsion preparations against four Acinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 32 publications
0
56
0
3
Order By: Relevance
“…It interacts with the negatively charged cell wall of the microbe by electrostatic attraction allowing the hydrophobic palmitate moiety of CPC to interact with the cell wall resulting in leakage of the cellular components 61 . Previous investigations indicated that CPC at 1.0 in a soybean nano-emulsion can inhibit the planktonic forms of Acinetobacter baumannii 62 . It was also used as antimicrobial and disinfecting agent in many commercially available oral hygiene products 63 and disinfecting soaps.…”
Section: Antimicrobial Activity Of Carvacrol Microemulsionmentioning
confidence: 96%
“…It interacts with the negatively charged cell wall of the microbe by electrostatic attraction allowing the hydrophobic palmitate moiety of CPC to interact with the cell wall resulting in leakage of the cellular components 61 . Previous investigations indicated that CPC at 1.0 in a soybean nano-emulsion can inhibit the planktonic forms of Acinetobacter baumannii 62 . It was also used as antimicrobial and disinfecting agent in many commercially available oral hygiene products 63 and disinfecting soaps.…”
Section: Antimicrobial Activity Of Carvacrol Microemulsionmentioning
confidence: 96%
“…8 Many studies have demonstrated the antimicrobial properties of nanoemulsions formulated with antimicrobial substances. 21 Investigations on the use of nanoemulsions as antimicrobial agents were prompted by the development of antimicrobial-resistant strains after the use of existing agents, due to the widespread and sometimes inappropriate use of antibiotics, disinfectants, and antiseptics. Moreover, nanoemulsions are novel water-inoil formulations that are stabilized by adding small amounts of surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol, sodium chloride and soybean oil, cetyl chloride are able to destroy the Acinetobacter baumannii biofilm. [38] Physical methods such as electric current, ultrasonic vibration, high-frequency pulse and heating can destroy the mature Acinetobacter baumannii biofilm to increase the antibiotic sensitivity to bacteria. Low frequency (0.4 MHz) ultrasound can promote the penetration of oxygen molecules and nutrients in the biofilm and accelerate the release of bacterial metabolites, resulting in the recovery of low-metabolizing bacteria and the restoration of sensitivity to antibiotics.…”
Section: Destruction Of the Formed Biofilm Of Acinetobacter Baumanniimentioning
confidence: 99%